2000
DOI: 10.1111/j.1749-6632.2000.tb06717.x
|View full text |Cite
|
Sign up to set email alerts
|

The Parahippocampal Region: Corticocortical Connectivity

Abstract: The parahippocampal region, as defined in this review, comprises the cortical regions that surround the rodent hippocampus including the perirhinal, postrhinal, and entorhinal cortices. The comparable regions in the primate brain are the perirhinal, parahippocampal, and entorhinal cortices. The perirhinal and postrhinal/parahippocampal cortices provide the major polysensory input to the hippocampus through their entorhinal connections and are the recipients of differing combinations of sensory information. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
372
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 456 publications
(386 citation statements)
references
References 42 publications
12
372
0
2
Order By: Relevance
“…From this and previous work (Burwell, 2000;Witter et al, 2000;Craig and Commins, 2007), clear predictions can be made in terms of the remaining projections and future work should focus on determining the electrophysiologically excitatory and inhibitory capabilities of the other projections in the hippocampal-parahippocampal network. We suggest, for example, that the projections from the proximal subiculum and lateral entorhinal to the perirhinal cortex will both be electrophysiologically excitatory in nature.…”
Section: Anatomical and Electrophysiological Evidence For Segregationmentioning
confidence: 55%
See 4 more Smart Citations
“…From this and previous work (Burwell, 2000;Witter et al, 2000;Craig and Commins, 2007), clear predictions can be made in terms of the remaining projections and future work should focus on determining the electrophysiologically excitatory and inhibitory capabilities of the other projections in the hippocampal-parahippocampal network. We suggest, for example, that the projections from the proximal subiculum and lateral entorhinal to the perirhinal cortex will both be electrophysiologically excitatory in nature.…”
Section: Anatomical and Electrophysiological Evidence For Segregationmentioning
confidence: 55%
“…There are a number of anatomical differences (Burwell et al, 1995;Burwell and Amaral, 1998a,b;Pitkä nen et al, 2000;Burwell, 2000Burwell, , 2001) and functional differences (Norman and Eacott, 2005) existing between the two areas and it has been suggested that the rat postrhinal cortex is homologous to the monkey parahippocampal cortex (Burwell et al, 1995;Burwell, 2000). Therefore, we follow Burwell's classification (2000) and distinguish between the perirhinal and postrhinal cortices as two distinct anatomical regions in the rat brain.…”
Section: Anatomical Definition Of the Perirhinal Cortexmentioning
confidence: 88%
See 3 more Smart Citations